Tribological study of hot pressed oxide dispersion strengthened 2205 DSS composite - Olaniran, O.; Olubambi, P. A.; Potgieter, J. H.; Omotoyinbo, J. A.; Obadele, B. A.; Andrew, A. (Acta Universitaria, 2014)
This work studied the influence of ceramic oxide on the tribological behavior of hot pressed 2205 DSS composites with varying percentage composition of partially stabilized zirconia (PSZ) and alloying elements; crome (Cr) with nickel (Ni) developed by PM route. The experiment was conducted with a tribometer by ball on disc under the following parameters: WC ball of 5 mm as the counterbody, sliding load of 15 N and sliding distance of 2 mm at room temperature under dry condition. Wear tracks of the worn surface were examined with Scanning Electron Microscope (SEM); JEOL JSM-7600F with Energy Dispersive X-ray Analysis (EDX) attachment. The results revealed that small amount of PSZ could enhance wear resistance of the composite. EDX spot analyses indicated that there were transferred layers of tungsten (W) on the worn surface. Coefficient of friction (COF) and Taber Index were used to evaluate the wear property of the composites. It was found that sample with 0.5% PSZ, 0.81% Cr and 0.19% Ni has the best wear resistance.
Keywords: Array; Array; Array; Array; Array